Delineation of Watersheds III Plain Areas - sharma, K D; Pathak, Supran (Annals of Arid Zone, 2016)
Watershed' is the basic planning unit for rural development in India. In this paper an Analytical Hierarchy Process (AHP) and multi-objective programming are integrated with Geographical Information System (GIS) to develop a decision support system for the delineation of watersheds in plain areaslzone of internal drainage frequently encountered in the Indian arid zone. The resultant technique settles the conflicts arising out of areas related to more than one drainage or more than one watersheds for the same outlet. This allows decision-maker's involvement and has application for similar scenario having many objectives and alternatives to be handled simultaneously.